Calcitonin and calcium ionophores: cyclic AMP responses in cells of a human lymphoid line. - Moran, J (1978)
Receptors for calcitonin, as assayed by the specific binding of 125I-labeled salmon calcitonin and stimulation of cyclic AMP formation, were found in 8866 cells derived from a human lymphoid line. The affinity of calcitonin from different species and of various analogues of human calcitonin for the binding sites and their ability to stimulate cyclic AMP formation were closely related to their hypocalcemic activity and presumably reflected biological properties of the hormones. Besides calcitonin, prostaglandin E1 and beta-adrenergic catecholamines stimulated cyclic AMP formation in these cells. The calcium ionophores, A23187 and Br-X-573A, did not influence the specific binding of 125I-labeled salmon calcitonin. A23187, however, suppressed basal and calcitonin-stimulated formation of cyclic AMP in the presence of at least 0.6 mM calcium in the incubation medium. Br-X-537A did not require extracellular calcium to suppress basal and calcitonin-stimulated formation of cyclic AMP, suggesting that the release of calcium from internal stores may regulate adenylyate cyclase activity in 8866 cells.